Effect of SP3OR on Increasing Community Participation in Sports (APMO) - Sandi Arisma Cipta Perdana Ilsya; Amung Mamun; Nurlan Kusmedi; Nuryadi Nuryadi (STKIP Muhammadiyah Kuningan, 2023)
The level of physical activity is the initial gate of a person's potential to have a group of fitness and health. The importance of the role of physical activity has led to the development of various studies, one of which was the birth of multiple programs designed to increase the participation of the sports community, such as the Undergraduate Program for Driving Sports Development (SP3OR). To determine the effectiveness of the SP3OR program, measurements were made with the Community Participation in Sports (APMO) indicator. The SP3OR program was carried out by involving 110 instructors divided into 27 districts/cities. The instructors provide treatment through exercise campaigns and joint sports in selected Villages/Kelurahan. The results showed an increase of 2.4%. In the calculation of the significance test with the T-test method, the result is 0.005, which means there is a significant change. The results of this study explain to the government at the Regency/City level, Province to the Central station, that the SP3OR program significantly impacts the community by increasing public interest in sports. Thus, it is hoped that it can be an example for other regions to implement programs that aim to increase the level of physical activity through sports which will ultimately have an impact on minimizing the risk of developing degenerative diseases